Chemotherapy drug shortages in paediatric oncology: A 14-year single-centre experience in Belgium. (December 2016) - Bauters, Tiene; Claus, Barbara OM; Norga, Koen; Huys, Isabelle; Simoens, Steven; Laureys, Geneviève
Shortages of chemotherapy are a growing challenge for the healthcare system. We present the burden of drug shortages of chemotherapeutics in the paediatric hemato-oncology unit of a tertiary care hospital and solutions that were used to manage them. Between January 2001 and December 2014, 54 individual shortages were detected, affecting a total number of 21 different drugs. In total, 4127 shortage days were registered with a mean duration of 196.5 SD ± 144.0 days per individual drug shortage. Methotrexate, doxorubicin and carboplatin had the longest supply disruptions. Solutions to address the problems were purchase of a generic alternative, a change of individual treatment plans, cohorting of patients and import from abroad.